Fairness Resource Sharing for Dynamic Workflow Scheduling on Heterogeneous Systems - Arabnejad, H.; Barbosa, J. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
For most Heterogeneous Computing Systems (HCS) the completion time of an application is the most important requirement. Many applications are represented by a workflow that is therefore schedule in a HCS system. Recently, researchers have proposed algorithms for concurrent workflow scheduling in order to improve the execution time of several applications in a HCS system. Although, most of these algorithms were designed for static scheduling, that is all application must be submitted at the same time, there are a few algorithms, such as OWM (online workflow Management) and RANK_HYBD, that were presented for dealing with dynamic application scheduling. In this paper, we present a new algorithm for dynamic application scheduling. The algorithm focus on the Quality of Service (QoS) experienced by each application (or user). It reduces the waiting and execution times of each individual workflow, unlike other algorithms that give privilege to average completion time of all workflows. The simulation results show that the proposed approach significantly outperforms the other algorithms in terms of individual response time.